An experimental study on the aggregation of TiO2 nanoparticles under environmentally relevant conditions - Romanello, Marina Belén (2013)
The eventual future scenario of a release of nanomaterials into the environment makes it necessary to assess the risk involved in their use by studying their behavior in natural waters. NanoTiO2 is one of the most commonly employed nanomaterials. In the present work we studied the aggregation rates, aggregate size and aggregate morphology of NanoTiO2 under the presence of inert electrolytes, divalent cations, and these two combined with natural organic matter, in an effort to provide a comprehensive investigation of the phenomena of interaction of nanomaterials and natural waters and elucidate some of the conflicting information reported in the literature. The stability of nanoparticles could be explained in all cases, at least qualitatively, in terms of classical DLVO interactions (Electrical Double Layer, Van der Waals). Divalent cations were adsorbed to the surface of the nanoparticles, neutralizing the negative charge at pH values greater than the point of zero charge and inducing aggregation. Natural organic matter (NOM) adsorbed to the particles and made their zeta potential more negative, hence stabilizing them by lowering the pH of maximum aggregation. Divalent cations partially neutralized the adsorbed NOM, and at high concentrations aggregation was observed with Ca2+ but not Mg2+, suggesting the presence of specific Ca2+–NOM bridges. SEM images visually revealed a fractal-like morphology of the aggregates formed under unfavorable conditions.